Variasi Bahasa dalam Whatsapp Grup Mahasiswa Semester VIIB Prodi Pendidikan Bahasa dan Sastra Indonesia Fakultas Ilmu Keguruan dan Pendidikan Universitas Muhammadiyah Bengkulu Tahun Ajaran 2022/2023 - Ajat Manjato; Rike Angreani; Wahyuni Shofinna Nur; Dika Zakiyah; Mutiara Widya Utami (Dinamika Pembelajaran : Jurnal Pendidikan dan bahasa, 2025)
This study aims to determine the use of language variations in terms of speakers (sociolect) in Semester VII B Students of the Indonesian Language and Literature Education Study Program, Faculty of Teacher Training and Education, Muhammadiyah University of Bengkulu, Academic Year 2022/2023. Based on these objectives, the method used in this study uses descriptive qualitative research. Data was collected through data obtained from student chat screenshots. The data collection technique in this thesis is a documentation technique in the form of screenshots. Data analysis techniques in this thesis are Data Identification, Data Classification, Data Analysis, Data Interpretation. Based on the results of the study, it can be concluded that theoretically there are 8 language variations based on the speaker's aspect (sociolect), namely 1. Acrolek, 2. Basilek, 3. Vulgar, 4. Slang, 5. Colloquial, 6. Jargon, 7. Argot, and 8. Ken. But based on research data, the type of use of language variations based on the speaker's point of view (siolect) used by WhatsApp Group members of students VII B of Indonesian Language and Literature Education Study Program Batch 2019 Muhammadiyah University of Bengkulu, obtained 114 data on 5 types of use of language variations, namely: 1. Acrolect found 7 data, 2. Basilek found 53 data 3. Slang found 28 data 4. Colloquial found 5 data and 5. Jargon found 21 data. Language variations that are often used by semester VII B students are basilek or regional language variations, because the group members come from different regions and many varieties of regional languages ​​are used.